Artificial Intelegence APLIKASI PEMILIHAN BERAS BERDASARKAN REFERENSI KONSUMEN MENGGUNAKAN FUZZY LOGIC - Rika Widya Perdana (Elkom : Jurnal Elektronika dan Komputer, 2021)
Rice is the most important staple food for humans to have energy to carry out activities. The purpose of this study is to provide information to the public in the form of a reference for selecting rice based on consumer interest, so that it can be used as a decision making in buying rice. The Mamdani method is a method that is able to solve problems in the case of rice selection based on consumer references. The work process of the Sugeno method consists of four parts, namely fuzification, inference engine, implication function amplification and the last one is defuzzification. The final result, the Mamdani method has the characteristics of using the AND operator and using the min-max value. This research is in the form of a decision-making system in rice selection based on references from consumers by looking at four aspects of criteria such as price, quality, taste, and shape variables, these four aspects can be used as a reference in rice selection. Sugeno fuzzy logic to get the final value.The Mamdani method is a very effective method in selecting rice according to the needs and interests of consumers so that potential consumers can easily choose rice according to their interests and desired criteria.